The Effect of Time Repetition Variation on Brain MRI Imaging Quality On T2 Weighted Sequences - Ade Rama Ditya Arsana Karang; Gusti Ngurah Sutapa; I Putu Surya Dharma Negara (Kappa Journal, 2024)
Magnetic Resonance Imaging (MRI) is an imaging technique used to produce images of parts of the human body by utilizing a strong magnetic field. The examination that is often carried out is a brain examination. This research was conducted at Bali Mandara Hospital. To find out the condition of the brain, an MRI examination can be done. MRI can produce images known as sequences which produce T1 Weighted Image (T1WI), T2 Weighted Image (T2WI), resulting in visible images with different intensities. To obtain T2WI, the time echo (TE) and time repetition (TR) must be long to give the fat and water a chance to decay, so that the fat and water contrast can be visualized well. This research aims to determine the effect of TR variations on SNR values, and determine the best TR to produce good image values. To generate T2WI SNRs on brain MRI. This street vendor activity uses a Phillips 1.5 Tesla type MRI aircraft. Data collection was obtained from twenty patients with 3 variations of TR values starting from 3,500 ms, 5,500 ms and 7,500 ms by obtaining a total of 60 images. Evaluate tissue SNR values by measuring ROI directly on the MRI device. SNR value analysis was performed on cerebrospinal fluid (CSF) tissue, spinal cord. Sequentially the SNR values obtained were 174.24, 211.22 and 244.51 in the CSF tissue 78.53, 80.64 and 84.81 in the spinal cord tissue. This street vendor activity has shown the result that the longer the TR value is given, the SNR value will increase. This is because long TR values are able to evaluate networks in more slices and provide better noise signal values. The TR variation of 7,500 ms can produce the highest SNR value so that the resulting image is very good